Establishing a Common Nutritional Vocabulary - From Food Production to Diet - Andrés-Hernández, Liliana; Blumberg, Kai; Walls, Ramona L.; Dooley, Damion; Mauleon, Ramil; Lange, Matthew; Weber, Magalie; Chan, Lauren; Malik, Adnan; Møller, Anders; Ireland, Jayne; Segovia, Lucia; et al. (Frontiers in Nutrition, 2022)
Informed policy and decision-making for food systems, nutritional security, and global health would benefit from standardization and comparison of food composition data, spanning production to consumption. To address this challenge, we present a formal controlled vocabulary of terms, definitions, and relationships within the Compositional Dietary Nutrition Ontology (CDNO, www.cdno.info) that enables description of nutritional attributes for material entities contributing to the human diet. We demonstrate how ongoing community development of CDNO classes can harmonize trans-disciplinary approaches for describing nutritional components from food production to diet.